Phase II trial of ponatinib in patients with bevacizumab‐refractory glioblastoma - Lee, Eudocia Q. (Cancer Med, 2019)
BACKGROUND: Responses to bevacizumab in glioblastoma (GBM) are not durable. Plasma levels of basic fibroblast growth factor (bFGF) increase at the time of tumor progression. By targeting vascular endothelial growth factor receptor (VEGFR), platelet‐derived growth factor receptor, Src, and FGF receptor pathways, ponatinib may potentially help to overcome some of the putative mechanisms of adaptive resistance. METHODS: We performed a phase II trial of ponatinib in patients with bevacizumab‐refractory GBM and variants. Adult patients with Karnofsky performance score (KPS) ≥60, measurable disease, and normal organ and marrow function received 45 mg ponatinib daily. No limit on the number of prior therapies but only one prior bevacizumab‐containing regimen was allowed. Primary endpoint was 3‐month progression‐free survival. Plasma biomarkers of angiogenesis and inflammation were evaluated before and after treatment. RESULTS: The study closed after the first stage. Fifteen patients enrolled: median age 61 [27‐74]; median KPS 80 [70‐90]; median number of prior relapses 2 [2‐4]. Three‐month progression‐free survival rate was 0, median overall survival was 98 days [95% CI 56, 257], and median PFS was 28 days [95% CI 27, 30]. No responses were seen. The most common grade ≥3 adverse events included fatigue (n = 3), hypertension (2), and lipase elevation (2). Ponatinib treatment significantly increased plasma VEGF, soluble (s)VEGFR1, sVEGFR2, sTIE2, interferon gamma (IFNγ), tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐6, IL‐8, and IL‐10 and decreased sVEGFR2. CONCLUSIONS: Ponatinib was associated with minimal activity in bevacizumab‐refractory GBM patients. Circulating biomarker data confirmed pharmacodynamic changes and suggested that resistance to ponatinib may be related to an increase in inflammatory cytokines.